The term 'Biosemiotik' in the 19th century. - Kull, Kalevi (Sign Systems Studies, 2022)
Tracing the emergence of biosemiotics, attention can be drawn to the very early usage of the term 'biosemiotics' (Biosemiotik) in the writings of Austrian chemist Vincenz Kletzinsky (1826--1882) that dates back to the 1850s. In the same decade, Kletzinsky also proved to be among the first to use the terms 'biochemistry' and 'biophysics'.